Electrically-tunable positioning of topological defects in liquid crystals - Sandford O’Neill, JJ; Salter, PS; Booth, M; Elston, S; Morris, S (Nature Research, 2020)
Topological defects are a consequence of broken symmetry in ordered systems and are important for understanding a wide variety of phenomena in physics. In liquid crystals (LCs), defects exist as points of discontinuous order in the vector field that describes the average orientation of the molecules in space and are crucial for explaining the fundamental behaviour and properties of these mesophases. Recently, LC defects have also been explored from the perspective of technological applications including self-assembly of nanomaterials, optical-vortex generation and in tunable plasmonic metamaterials. Here, we demonstrate the fabrication and stabilisation of electrically-tunable defects in an LC device using two-photon polymerisation and explore the dynamic behaviour of defects when confined by polymer structures laser-written in topologically discontinuous states. We anticipate that our defect fabrication technique will enable the realisation of tunable, 3D, reconfigurable LC templates towards nanoparticle self-assembly, tunable metamaterials and next-generation spatial light modulators for light-shaping.